The Effect of Experiment Methods on Student Learning Results in Learning IPA in Class VIII Mts. Negeri 2 Labuan - Upi Hanapiah (Reflection: Education and Pedagogical Insights, 2023)
This study aims to analyze how much influence the experimental method has on the learning outcomes of students in class VIII MTs. Negeri 2 Labuan. The research method used is the experimental method, with the form of quasi exsperimental design with the type of time series design. The sample of this study was 25 students. Based on the results of statistical calculations show that the average student post-test learning outcomes of 73.22. The results of hypothesis testing obtained 4.8138 (tcount> ttable) so that it is declared accepted. From the calculation of effect size obtained 1.5379 (high). This means that the experimental learning method has a high influence on student learning outcomes in class VIII MTs. Negeri 2 Labuan. Keywords: Experimental Learning Method, Learning Outcomes